Code-mixing and language dominance: bilingual, trilingual and multilingual children compared. Issue 4 (2nd October 2019) - Poeste, Meike; Müller, Natascha; Arnaus Gil, Laia
ABSTRACT: Acquisitionists generally assume a relation between code-mixing in young bilingual and trilingual children and language dominance. In our cross-sectional study we investigated the possible relation between code-mixing and language dominance in 122 children raised in Spain or Germany. They were bilingual, trilingual or multilingual, the latter acquiring more than three languages. The definition of language dominance is grounded on Birdsong's (2014. Dominance in bilingualism: Foundations of measurement, with insights from the study of handedness. In C. Silva-Corvalán, & J. Treffers-Daller (Eds.), Language Dominance in Bilinguals: Issues of operationalization and measurement (pp. 85–105). Cambridge: Cambridge University Press) distinction between domains and dimensions. The main result of our study is that code-mixing is rare in a monolingual setting which means that bilingual, trilingual and multilingual children are able to behave monolingually. Domain-specific language dominance can explain the relatively high mixing rate in the Catalan tests but concerning the dimensions of language dominance no relation was found between the children's code-mixing and language (un)balance. A separate analysis of intra- and intersentential mixing reveals that intersentential mixing is determined by the typological proximity between the child's languages. All instances of intrasentential code-mixing, were insertional.